2019
DOI: 10.1055/a-1062-6167
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients Symptomatically Unresponsive to Levothyroxine: Natural Desiccated Thyroid Extract or the Combination of Levothyroxine and Liothyronine? A Research Priority

Abstract: Around 5–10% of hypothyroid patients continue to experience profound and sometimes disabling symptoms, including fatigue, depression and impaired cognition, in spite of being adequately replaced biochemically. The use of the combination of levothyroxine and liothyronine and natural desiccated thyroid extract is controversial for reasons of costs, a lack of evidence of additional benefit over levothyroxine alone, and potential safety concerns. Clinical guidelines caution against the use of both, and advise that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…At present, it remains to be seen what proportion of these will benefit from liothyronine either in its current form or in the form of newer longer acting preparations currently under development. Certainly, recent evidence has shown that a small but significant proportion of people treated for hypothyroidism remain actively symptomatic 18,19 . Interestingly, it is noteworthy that even in the 1970s it was recognized that some patients did not feel well on levothyroxine monotherapy and seemed to prefer liothyronine being used in combination with levothyroxine 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, it remains to be seen what proportion of these will benefit from liothyronine either in its current form or in the form of newer longer acting preparations currently under development. Certainly, recent evidence has shown that a small but significant proportion of people treated for hypothyroidism remain actively symptomatic 18,19 . Interestingly, it is noteworthy that even in the 1970s it was recognized that some patients did not feel well on levothyroxine monotherapy and seemed to prefer liothyronine being used in combination with levothyroxine 20 …”
Section: Discussionmentioning
confidence: 99%
“…Certainly, recent evidence has shown that a small but significant proportion of people treated for hypothyroidism remain actively symptomatic. 18,19 Interestingly, it is noteworthy that even in the 1970s it was recognized that some patients did not feel well on levothyroxine monotherapy and seemed to prefer liothyronine being used in combination with levothyroxine. 20 Decisions concerning the formulary restriction, deprescribing or…”
Section: Costmentioning
confidence: 99%
“…Published clinical trials and systematic reviews 9 16 were assessed for relevant data on the clinical effectiveness of liothyronine/levothyroxine combination therapy. None of the trials restricted their inclusion criteria to (or performed a subgroup analysis of) the population of interest and were therefore not considered relevant to inform the decision problem.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical guidelines acknowledge the limited evidence-base for liothyronine. While 13 trials of combination versus levothyroxine monotherapy therapy have been reported,9 the majority are underpowered, some are unlikely to have tested the correct dose of liothyronine, and none restricted recruitment to patients who did not feel significantly better on levothyroxine alone 3 9–12. This latter point could explain why liothyronine/levothyroxine combination therapy has not demonstrated superiority, even in the larger trials.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that 5-10% of hypothyroid patients receiving LT4 continue to experience disabling symptoms such as fatigue, depression, and impaired cognition, despite being adequately replaced biochemically, affecting their quality of life [4]. In a study that aimed to evaluate satisfaction and quality of life (QOL) in 969 hypothyroid patients through a survey, it was found that 77.6% were dissatisfied, and the scores of QOL were low.…”
Section: Introductionmentioning
confidence: 99%